The Effect of Leverage and Company Size on Company Value Moderated by Corporate Social Responsibility (CSR) (Case Study on LQ 45 Stock Company 2017-2019) - Dewi Saptantinah Puji Astuti; Djoko Kristianto; Hesti Setyoningsih (Budapest International Research and Critics University, 2022)
Firm value is the investor's perception of the company, which is often associated with stock prices. Firm value can be increased through several indicators, including leverage, company size, and corporate social responsibility. The purpose of this study was to determine the effect of leverage and firm size on firm value with CSR as a moderating variable. This study uses secondary data sources. The population in this study is the LQ45 stock company for the 2017-2019 period. The samples obtained were 23 companies using the purpose sampling method. The data analysis technique used is descriptive statistical analysis, classical assumption test, hypothesis testing and absolute difference analysis test. The results of the study concluded that leverage has a positive and significant effect on firm value, firm size has a positive and significant effect on firm value. CSR cannot moderate the effect of leverage and firm size on firm value in companies that are members of LQ45 shares for the 2017-2019 period.